Post-mortem CT for coronial death investigation: a local authority managed service evaluation - Kelly, Keiran; England, L.; Viner, Mark (Elsevier, 2026)
Introduction Post-mortem CT (PMCT) is increasingly used in coronial death investigations. This service evaluation assesses the new PMCT service at the East London Forensic Centre (ELFC), focusing on turnaround times, conversion rates to invasive post mortems, and radiology-pathology concordance. The goal is to measure key performance indicators and guide future service development. Methods Data from 356 cases were retrospectively reviewed using emails, Civica, and a PMCT log. Information on scan and report timings, conversion rates, and radiology-pathology agreement was analysed. The impact of contrast-enhanced PMCT on workflow was also assessed. Timing data were grouped into September–January, with January separated due to holiday-related delays. Forensic and non-East London cases were excluded. Results Of the 356 cases, 35% underwent angiography. Unenhanced scans averaged just under 13 min; angiography scans took nearly 30 min. 15% required further invasive examination. Among these, nearly 80% showed at least partial radiology pathology concordance, with 6 fully concordant cases. The average turnaround from start to cause of death determination was 4.2 days. Conclusion PMCT is an effective alternative to traditional post-mortems, though 15% of cases still required invasive follow-up. Most showed good radiology-pathology agreement. Delays in January highlight operational challenges. ELFC’s turnaround aligns with other services, affirming PMCT’s feasibility in coronial settings. Continuous refinement of case selection is needed to reduce conversion rates. Further research should explore PMCT failure rates and compare outcomes with traditional post-mortems. Implications for practice The service evaluation supports a local authority managed service which compares to existing, successful models elsewhere in the country
Keywords: 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Biomedical Imaging; 3199 Other biological sciences